A Human Head and Neck Squamous Cell Carcinoma Cell Line with Acquired cis-Diamminedichloroplatinum-Resistance Shows Remarkable Upregulation of BRCA1 and Hypersensitivity to Taxane. (20th October 2011) - Saiki, Yuriko; Ogawa, Takenori; Shiga, Kiyoto; Sunamura, Makoto; Kobayashi, Toshimitsu; Horii, Akira
Abstract : Recently, an inverse relationship between resistance to platinum-based chemotherapeutic agents and taxanes has been implicated in breast and ovarian cancers, and a possible pivotal role for BRCA1 has also been suggested. Because cis -diamminedichloroplatinum (CDDP) and taxanes are the most active antitumor agents against head and neck squamous cell carcinoma (HNSCC), we analyzed the sensitivity of nine HNSCC cell lines and their previously established derived CDDP-resistant cell lines to two representative taxanes: docetaxel and paclitaxel. None of the nine original cell lines showed any cross resistance between CDDP and taxanes, but one of the CDDP-resistant cell lines, RPMI2650CR, demonstrated hypersensitivity to both taxanes when compared to the parental cell line, RPMI2650. Furthermore, RPMI2650CR exhibited increased expression of BRCA1. These data suggest that (i) taxanes are a good candidate for a second-line therapeutic drug for HNSCC patients with acquired CDDP resistance and (ii) BRCA1 can be a candidate marker for predicting an inverse CDDP/taxane sensitivity phenotype in HNSCC.